AESTHETIC SPACE IN SYNTHETIC CUBISM, INTERPRETATION ANALYSIS OF ARMEN NAZARUDDIN'S PAINTINGS - Mukhsin Patriansah; Ria Sapitri; Husni Mubarat (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
This study aims to see the aesthetic spaces in synthetic cubism by Armen Nazaruddin. When mastering the techniques, tools and materials that are mastered, the next problem that arises is the application of aesthetic values in the form of works of art. Therefore, describing an experience of having a sense and being intellectual in giving birth to his work of art. This is what the author did to conduct an object study of Armen Nazaruddin's painting, which later could be used as a reference and reference in the development of painting in Indonesia, especially in West Sumatra. This painting really considers the principles of making principles in detail and meticulously as well as the stars of the message and meaning in it. Artists experiment with how to make use of objects around them that have no value to become more appropriate in accordance with the Minang Kabau philosophy, namely,